2012
DOI: 10.1371/journal.pgen.1002491
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis and Genome-Wide Association Study of Platelet Count and Mean Platelet Volume in African Americans

Abstract: Several genetic variants associated with platelet count and mean platelet volume (MPV) were recently reported in people of European ancestry. In this meta-analysis of 7 genome-wide association studies (GWAS) enrolling African Americans, our aim was to identify novel genetic variants associated with platelet count and MPV. For all cohorts, GWAS analysis was performed using additive models after adjusting for age, sex, and population stratification. For both platelet phenotypes, meta-analyses were conducted usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
90
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 65 publications
(92 reference statements)
5
90
0
Order By: Relevance
“…This plot shows, for example, multiple associations on chromosome 10 in gene JMJD1C to be associated with platelet mean volume as well as alkaline phosphatase (red box on Figure 4). Different GWAS studies performed separately on blood and metabolic panels have identified these associations 23,24 and our study serves as confirmation for these associations when both panels are combined together and analysis is run on the same patients. In our analysis, we see opposite directions of effect for both of these associations, i.e.…”
Section: Resultssupporting
confidence: 67%
“…This plot shows, for example, multiple associations on chromosome 10 in gene JMJD1C to be associated with platelet mean volume as well as alkaline phosphatase (red box on Figure 4). Different GWAS studies performed separately on blood and metabolic panels have identified these associations 23,24 and our study serves as confirmation for these associations when both panels are combined together and analysis is run on the same patients. In our analysis, we see opposite directions of effect for both of these associations, i.e.…”
Section: Resultssupporting
confidence: 67%
“…2011; Qayyum et al . 2012). For livestock, however, there is a potential for violations of this assumption when medium density chips are used in low LD populations.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of these differences is still unknown. While environmental factors and life styles have been suggested to explain the differences [28][29], genetic factors may also play a role [27,33]. Besides, the possible influencing factors may also including the special diet habit, climate and the life styles of the basin, which deserve our next exploring work.…”
Section: Discussionmentioning
confidence: 96%
“…Emerging evidence has shown that MPV, which was a measurement of the average size of platelet parameter, but generally overlooked, may be a risk factor of immunity, inflammation and angiogenic diseases [28][29]. However, MPV reference ranges are not identical between different regions and populations.…”
Section: Discussionmentioning
confidence: 99%